Why "Dissident" Irish Republicans Haven't Gone Away: A Visual Study of the Persistence of "Terrorism". Issue 1 (1st June 2021) - White, Robert W.
Abstract: When considering "terrorists" and "terrorism, " the focus tends to be on violence—the threat of violence, its aftermath, the ideology and belief systems that lead to it, and so forth. Political violence, however, represents only a portion of the repertoire of collective action that is available to "terrorists." Images from "dissident" Irish Republican events and photo-elicitation interviews with activists who participated in these events show that: (1) the repertoire of "violent" organizations includes nonviolent political activity; and (2) the organizational structures and affective incentives that sustain activism in nonviolent voluntary associations and social movement organizations also sustain activism in organizations that embrace physical force or "terrorism." In combination, these findings show that "dissident" Irish Republicans are likely to persist into the foreseeable future. More generally, the findings also show that our understanding of "terrorists" and "terrorist organizations" will be enhanced if we focus less on their violent activities and more on their similarities with nonviolent activists and organizations.